Climate Responsiveness and Thermal Performance of Roma Tabing Tongkok Vernacular Houses in Situbondo, Indonesia - Datin Kamilah Nurlaily; Nugroho, Agung Murti; Yusran, Yusfan Adeputera; bin Kandar, Mohd Zin (Civil and Environmental Science Journal (CIVENSE), 2025)
Roma Tabing Tongkok, a vernacular house of the Madurese Pendalungan community in Situbondo, reflects local adaptation to the region’s hot-dry climate. This study aimed to examine its climate-responsive features and thermal comfort performance using a mixed-method approach combining visual analysis with temperature and humidity measurements conducted over two months (October–November 2023). Results shows that the house’s linear form, natural materials, and cross-ventilation openings support climate adaptation, yet their effectiveness remains limited due to suboptimal building orientation, lack of shading, and variations in roof height that affect heat release. These findings highlight the need to integrate additional passive strategies, such as low-conductivity ceilings, vegetation as a shading, and improved opening orientation to enhance thermal comfort. Strengthening these design adaptations can help sustain vernacular architecture while offering a model for energy-efficient, climate-responsive housing in dry tropical regions.